Associations of LH and FSH with reproductive hormones depending on each stage of the menopausal transition - Takako Kawakita; Toshiyuki Yasui; Kanako Yoshida; Sumika Matsui; Takeshi Iwasa (BMC Women's Health, 2023)
Abstract Introduction Associations of luteinizing hormone (LH) with androgens during the menopausal transition and associations between follicle-stimulating hormone (FSH) levels and various diseases related to reproductive hormones in postmenopause have received much attention. LH and FSH are also known to be associated with activities of enzymes related to reproductive hormones. We examined the associations of LH and FSH with androgens and estrogens in each stage of the menopausal transition according to a classification from menopausal transition to postmenopause. Methods This study was a cross-sectional design. We basically used the Stage of Reproductive Aging Workshop (STRAW) + 10. We divided the 173 subjects into 6 groups according to menstrual regularity and follicle-stimulating hormone level: mid reproductive stage (Group A), late reproductive stage (Group B), early menopausal transition (Group C), late menopausal transition (Group D), very early postmenopause (Group E) and early postmenopause (Group F). Levels of LH, FSH, dehydroepiandrosterone sulfate (DHEAS), estradiol, estrone, testosterone (T), free T, androstenedione and androstenediol were measured. Results In Group A, LH showed significant positive correlations with androstenedione and estrone. In Group D, LH was positively associated with T and free T and was negatively associated with estradiol. In Groups B, C, D and F, LH showed significant positive correlations with FSH, and there was a tendency for an association between LH and FSH in Group E. FSH was associated with estradiol but not with estrone in Groups C and D. Conclusion The associations of LH and FSH with reproductive hormones are different depending on the stage of the menopausal transition. Trial registration Trial registration number 2356-1; Date of registration: 18/02/2018, retrospectively registered.